Deep Sequencing of a Systematic Peptide Library Reveals Conformationally‐Constrained Protein Interface Peptides that Disrupt a Protein‐Protein Interaction. (7th December 2021) - Boragine, David M.; Huang, Wanzhi; Su, Lynn H.; Palzkill, Timothy
Abstract: Disrupting protein‐protein interactions is difficult due to the large and flat interaction surfaces of the binding partners. The BLIP and BLIP‐II proteins are unrelated in sequence and structure and yet each potently inhibit β‐lactamases. High‐throughput oligonucleotide synthesis was used to construct a 12, 470‐member library containing overlapping linear and cyclic peptides ranging in size from 6 to 21 amino acids that scan through the sequences of BLIP and BLIP‐II. Phage display affinity selections and deep sequencing revealed that, despite the differences in interaction surfaces with β‐lactamases, rapid enrichment of consensus peptide regions originating from both BLIP and BLIP‐II contact residues in the binding interface occurred. BLIP and BLIP‐II peptides that were enriched by affinity selection were shown to bind β‐lactamases and disrupt the BLIP/β‐lactamase interaction. The results suggest that peptides that bind at and disrupt PPI interfaces can be identified through systematic peptide library construction, affinity selection, and deep sequencing. Abstract : Disrupting protein‐protein interactions is difficult due to the large and flat interaction surfaces of the binding partners. We utilized high throughput oligonucleotide synthesis, peptide phage display library construction, affinity selection, and deep sequencing to show a peptide library encompassing a binding partner in a protein‐protein interaction can serve as a source of peptides that mimic the interface and provide a starting point for developing inhibitors that block the interface.